Outcomes of patients with EGFR-mutant advanced NSCLC in a developing country in Southeast Asia - How, Soon Hin; Chong, Kin Liam; Zainal Abidin, Muhammad 'Adil; Hasbullah, Harissa H; Lye, Mun Tho; Gwo, Fuang Ho; Muhamad Nor, Ibtisam; Yong, Kek Pang; Kean, Fatt Ho; Thiagarajan, Muthukkumaran; Ariffin, Roziana; Samsudin, Azlina; et al. (Dove Medical Press Ltd, 2022)
Background: Although first- and second-generation EGFR TKIs are considered first-line treatment in EGFRm+ NSCLC, most patients develop resistance and progress, commonly, EGFR T790M mutation. The third-generation EGFR-TKI has demonstrated efficacy in patients with progressive disease harboring the T790M mutation and in the first-line setting, bypassing this mode of resistance. The primary objectives of this study are to describe the proportion of EGFRm+ NSCLC patients treated with first-, second- and third-generation EGFR TKIs, and cytotoxic chemotherapy in the first-line setting, and the time on treatment for each category. Secondary objectives are to determine the dropout rate, the rates for T790M mutation testing at disease progression and the type of subsequent treatment. Methods: This multicenter retrospective study utilized data from the Malaysian Lung Cancer Registry that actively registers all lung cancer patients ≥18 years, with primary lung cancer confirmed histologically or cytologically. All patients diagnosed with advanced stages (ie stages IIIB, IIIC and IV) EGFRm+ NSCLC from 1st of January 2015 to 31st December 2019 were included. Results: Of 406 patients with EGFRm+ NCSLC, 351 were treated. Types of first-line treatment were as follows: EGFR-TKIs (first generation – 54.1%, second generation – 25.6% and third-generation – 12.5%) and chemotherapy (7.7%). The median time of treatment for each generation of EGFR-TKI was 12 months, 12 months and 24 months, and 2 months for chemotherapy. The dropout rate was 28.7% (n = 101). Nearly half (49.4%) of patients who were on first- or second-generation EGFR-TKI had further genetic testing via liquid or tissue biopsies upon disease progression. About 24.9% of those who developed disease progression after firstor second-generation EGFR TKI were started on a third-generation EGFR TKI. Conclusion: In the real-world, the management of EGFRm+ advanced NSCLC patients in an Asian cost-restrictive setting may adversely affect the choice of first-line therapy, time on each line of treatment and subsequently the overall survival of patients. Keywords: tyrosine kinase inhibitors, lung cancer, time on treatment, overall survival